Strategi Adaptasi UMKM Berbasis Rumahan dalam Meningkatkan Daya Saing Usaha di Kota Makassar: Studi Fenomenologi terhadap Pemanfaatan Aplikasi Digital sebagai Pengganti Ruko - Syahrul Syahrir Warham; Ulul Azmi Mustari; M Fikri Alghifari Yunus (CV Global Research Publication, 2026)
This study aims to describe and analyze the adaptation strategies carried out by home-based MSME (Micro, Small, and Medium Enterprises) actors in Makassar City in utilizing their homes and digital applications as substitutes for physical stores (ruko), as well as to analyze the role of these strategies in improving business competitiveness. This phenomenon emerged as a response to limited business capital and the high cost of renting business premises in urban areas, where MSME actors choose to use their private homes as production sites while relying on delivery applications and social media as marketing and distribution channels, without serving direct walk-in customers. This study employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, observation, and documentation involving 8 (eight) home-based MSME informants in Makassar City with varying ages and business types (culinary, fashion, and handicrafts), selected using purposive sampling. The findings reveal that home-based MSME actors in Makassar City implement adaptation strategies through three main aspects: optimizing the home as a resource substitute for a physical store, adopting digital applications gradually according to each individual’s readiness, and adjusting economic behavior such as pricing strategies and customer trust management.